Revitalisasi Tradisi Rebo Wekasan Sebagai Sarana Penanaman Nilai-Nilai Keislaman Di Masyarakat - Chairudin, Mochamad (Proceedings of Annual Conference for Muslim Scholars, 2024)
The Rebo Wekasan tradition is a religious practice held on the last Wednesday of the month of Safar in the Islamic calendar. Although its meaning has shifted over time, it remains essential for instilling Islamic values in society. This study uses qualitative methods and a case study approach to revitalize the Rebo Wekasan Tradition in Suci Village, Manyar, Gresik, East Java. The findings suggest that revitalization can be achieved by enhancing community understanding, involving the younger generation, and fostering collaboration between traditional stakeholders, religious leaders, and local authorities. These efforts aim to reinforce Islamic values, such as unity, social awareness, and devotion to Allah SWT, within the Suci Village community